(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
One of the areas in which language interacts with culture in the text is this precendent. One lives in an infinite duration of previous texts relative to each newly created text. This article provides views on the substitution of parems in the text and comments on the order of application.